Effects of Passive Leadership in the Digital Age - Wang, Cheng-Hui; Liu, Gloria H. W.; Lee, Neil Chueh-An (Frontiers in Psychology, 2021)
Nowadays organizations must adapt themselves to the trend of digitalization. Social media engagement editors emerge as a new role crucial for organizational growth and prosperity in the digital age. Engagement editors are usually tasked to facilitate the functions of marketing, content production, and data analysis. They have to manage online community, and handle online audiences’ frequent toxic and aggressive behaviors. Engagement editors thus are prone to emotional stress. Substantial literature has examined the influence of leadership style on employee performance. However, passive leadership is rarely studied. This research investigates (1) whether passive leadership would negatively affect engagement editors’ performance (i.e., online interaction with audiences); and (2) how the negativity would be ameliorated by job autonomy and employee resilience from the conservation of resource perspective. We surveyed 122 engagement editors and used the SmartPLS 3.2.9 to analyze the data. This research provides useful implication for managing engagement editors.